Counseling and Assistance in Making Ovitrap with the Principle of Re use To control Aedes aegypti larvae - Ratna Dian Kurniawati; Agung Sutriyawan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Dengue hemorrhagic fever (DHF) is still a health problem, especially in endemic areas. Aedes aegypti mosquito as a vector for the dengue virus needs serious attention. The 3M Plus Mosquito Nest Eradication has been promoted by the government as a preventive effort to increase the incidence of dengue fever. The purpose of this community service is to increase the knowledge of housewives (IRT) through the implementation of counseling and assistance in making ovitrap with the principle of reuse to reduce the population of Aedes aegypti larvae. This community service was carried out with an intervention approach in a one group pretest-posttest design experimental design. The location of community service is in RW 04, Cisaranteun Endah Village at 199 IRT. Most of the IRT (53.3%) before attending the counseling had less knowledge and after attending the counseling most of the IRT (69.3%) had good knowledge. The average score before counseling was 50.28 with a standard deviation of 15.518 and the average score after counseling was 81.08 with a standard deviation of 10.325, and the p-value was 0.000. This means that there is a significant difference in the level of knowledge of IRT before and after being given counseling and assistance. The goal of community service is to achieve a significant increase in IRT knowledge about ovitrap as a means of controlling the population of Aedes aegyti mosquito larvae, how to make it and provide assistance in making ovitrap with the principle of Re-use.